let V be RealLinearSpace; :: thesis: for v1, v2, v3 being VECTOR of V
for L being Linear_Combination of V st L is convex & Carrier L = {v1,v2,v3} & v1 <> v2 & v2 <> v3 & v3 <> v1 holds
( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 & Sum L = (((L . v1) * v1) + ((L . v2) * v2)) + ((L . v3) * v3) )

let v1, v2, v3 be VECTOR of V; :: thesis: for L being Linear_Combination of V st L is convex & Carrier L = {v1,v2,v3} & v1 <> v2 & v2 <> v3 & v3 <> v1 holds
( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 & Sum L = (((L . v1) * v1) + ((L . v2) * v2)) + ((L . v3) * v3) )

let L be Linear_Combination of V; :: thesis: ( L is convex & Carrier L = {v1,v2,v3} & v1 <> v2 & v2 <> v3 & v3 <> v1 implies ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 & Sum L = (((L . v1) * v1) + ((L . v2) * v2)) + ((L . v3) * v3) ) )
assume that
A1: L is convex and
A2: Carrier L = {v1,v2,v3} and
A3: ( v1 <> v2 & v2 <> v3 & v3 <> v1 ) ; :: thesis: ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 & Sum L = (((L . v1) * v1) + ((L . v2) * v2)) + ((L . v3) * v3) )
reconsider L = L as Linear_Combination of {v1,v2,v3} by ;
consider F being FinSequence of the carrier of V such that
A4: ( F is one-to-one & rng F = Carrier L ) and
A5: ex f being FinSequence of REAL st
( len f = len F & Sum f = 1 & ( for n being Nat st n in dom f holds
( f . n = L . (F . n) & f . n >= 0 ) ) ) by A1;
consider f being FinSequence of REAL such that
A6: len f = len F and
A7: Sum f = 1 and
A8: for n being Nat st n in dom f holds
( f . n = L . (F . n) & f . n >= 0 ) by A5;
len F = card {v1,v2,v3} by ;
then A9: len f = 3 by ;
then A10: dom f = {1,2,3} by ;
then A11: 1 in dom f by ENUMSET1:def 1;
then A12: f . 1 = L . (F . 1) by A8;
then f /. 1 = L . (F . 1) by ;
then reconsider r1 = L . (F . 1) as Element of REAL ;
A13: 3 in dom f by ;
then A14: f . 3 = L . (F . 3) by A8;
then f /. 3 = L . (F . 3) by ;
then reconsider r3 = L . (F . 3) as Element of REAL ;
A15: 2 in dom f by ;
then A16: f . 2 = L . (F . 2) by A8;
then f /. 2 = L . (F . 2) by ;
then reconsider r2 = L . (F . 2) as Element of REAL ;
A17: f = <*r1,r2,r3*> by ;
then A18: ((L . (F . 1)) + (L . (F . 2))) + (L . (F . 3)) = 1 by ;
now :: thesis: ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 )
per cases ( F = <*v1,v2,v3*> or F = <*v1,v3,v2*> or F = <*v2,v1,v3*> or F = <*v2,v3,v1*> or F = <*v3,v1,v2*> or F = <*v3,v2,v1*> ) by A2, A3, A4, Lm13;
suppose A19: F = <*v1,v2,v3*> ; :: thesis: ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 )
then A20: F . 3 = v3 by FINSEQ_1:45;
( F . 1 = v1 & F . 2 = v2 ) by ;
hence ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 ) by A7, A8, A11, A15, A13, A12, A16, A14, A17, A20, RVSUM_1:78; :: thesis: verum
end;
suppose A21: F = <*v1,v3,v2*> ; :: thesis: ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 )
then A22: F . 3 = v2 by FINSEQ_1:45;
( F . 1 = v1 & F . 2 = v3 ) by ;
hence ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 ) by A8, A11, A15, A13, A12, A16, A14, A18, A22; :: thesis: verum
end;
suppose A23: F = <*v2,v1,v3*> ; :: thesis: ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 )
then A24: F . 3 = v3 by FINSEQ_1:45;
( F . 1 = v2 & F . 2 = v1 ) by ;
hence ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 ) by A7, A8, A11, A15, A13, A12, A16, A14, A17, A24, RVSUM_1:78; :: thesis: verum
end;
suppose A25: F = <*v2,v3,v1*> ; :: thesis: ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 )
then A26: F . 3 = v1 by FINSEQ_1:45;
( F . 1 = v2 & F . 2 = v3 ) by ;
hence ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 ) by A8, A11, A15, A13, A12, A16, A14, A18, A26; :: thesis: verum
end;
suppose A27: F = <*v3,v1,v2*> ; :: thesis: ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 )
then A28: F . 3 = v2 by FINSEQ_1:45;
( F . 1 = v3 & F . 2 = v1 ) by ;
hence ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 ) by A8, A11, A15, A13, A12, A16, A14, A18, A28; :: thesis: verum
end;
suppose A29: F = <*v3,v2,v1*> ; :: thesis: ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 )
then A30: F . 3 = v1 by FINSEQ_1:45;
( F . 1 = v3 & F . 2 = v2 ) by ;
hence ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 ) by A8, A11, A15, A13, A12, A16, A14, A18, A30; :: thesis: verum
end;
end;
end;
hence ( ((L . v1) + (L . v2)) + (L . v3) = 1 & L . v1 >= 0 & L . v2 >= 0 & L . v3 >= 0 & Sum L = (((L . v1) * v1) + ((L . v2) * v2)) + ((L . v3) * v3) ) by ; :: thesis: verum